Effects of reasoning demands triggered by genre on Chinese EFL learners' writing performance - Peng, Cheng; Bao, Zhen (Frontiers in Psychology, 2023)
Introduction Genres, having distinct communicative functions, elicit different levels of reasoning demands in writing tasks. The current study investigated the influence of cognitive complexity triggered by a seldom studied pair of genres (expository writing vs. argumentative writing) on Chinese advanced EFL learners' writing performance. Method A total of 76 L2 learners participated in two writing tasks: one simpler expository writing task involving fewer reasoning demands and the other more complex argumentative writing task eliciting more reasoning demands. Multiple measure indices were adopted to comprehensively reflect the differences in production dimensions between the two writing tasks, such as lexical complexity, syntactic complexity, accuracy, fluency, and cohesion. Results and discussion The results showed that cognitive complexity significantly improved lexical complexity, clausal complexity, and cohesion, which generally supported the Cognition Hypothesis. However, phrasal structures and clausal structures within the construct of syntactic complexity displayed a trade-off effect, partially corroborating the Trade-off Hypothesis. Accuracy and fluency were uninfluenced, verifying neither of these hypotheses. Implications for sequencing and designing L2 writing tasks were provided for relevant stakeholders.